Preparation and evaluation of acryloyl morpholine modified emulsion fracturing fluid thickener with high temperature resistance and salt resistance - Shi, Shenglong; Sun, Jinsheng; Lv, Kaihe; Wen, Qingzhi; Bai, Yingrui; Wang, Jintang; Jin, Jiafeng; Liu, Jingping; Huang, Xianbin; Li, Jian (Journal of applied polymer science, 2023)
To prepare the thickener of fracturing fluid with temperature resistance, salt resistance and quick dissolution, an emulsion thickener (ASC) was synthesized by acrylamide, acrylic acid, 2‐acrylamide‐2‐methylpropanesulfonic acid, and acryloyl morpholine. The dissolution, salt resistance and drag reduction of ASC, and the viscoelasticity, temperature resistance and shear resistance and gel breaking properties of fracturing fluid formed by ASC and zirconium crosslinker were investigated. The results showed that the sticky time of ASC was less than 60 s and the drag reduction rate was 72.5% in 100,000 mg/L brine, showing that ASC had thickening ability in high salinity brine and satisfied the requirements of continuous fluid preparation on the fracturing process. The viscosity of ASC fracturing fluid was 98 mPa s after shearing at 200°C and 170 s−1 for 150 min when the salinity was 100,000 mg/L. When the ammonium persulfate concentration was 400 mg/L, the viscosity of the broken fluid was 4.0 mPa s. The temperature resistance, salt resistance and shear resistance of ASC emulsion fracturing fluid could be significantly improved by the introduction of acryloyl morpholine, ASC fracturing fluid had the characteristics of high elasticity and low viscosity, which could meet the application requirements under ultra‐high temperature reservoirs. A new type of emulsion polymer thickener ASC with high temperature resistance, salt resistance, quick dissolution and high drag reduction at the same time was prepared, 2‐acrylamide‐2‐methylpropanesulfonic acid and acryloyl morpholine were introduced to improve the temperature resistance and salt resistance of ASC. The thickener ASC could be used as a multi‐functional fracturing fluid, it played a slick water role in drag reduction effect at low polymer concentration (0.08–0.12 wt%), and it played a high viscosity fracturing fluid role in sand carrying effect at high polymer concentration (2.0 wt%) used together with organic zirconium crosslinker for ultra‐high temperature reservoirs even at 200°C and salinity of 100,000 mg/L, which could meet the application requirements under ultra‐high temperature reservoirs.